Changes in position and relationship between jaws in children treated with Delair's mask - Glišić Branislav; Šćepan Ivana; Nikolić Zorana; Đorđević Dušan (Serbian Medical Society - Dental Section, Belgrade, 2004)
The aim of this study was to examine the efects of Delair`s mask on facial skeleton in patients with Class III antero-posterior jaw relationship. Two groups of children were evaluated. The first group of 34 children with Class III was treated with Delair`s mask. The second group of 46 children with Class III did not receive any orthodontic treatment and was presented as a control group. In the first group pretreatment and post treatment radiographic tracing was done while second tracing in the control group was done a year after diagnostic radiographic tracing. Analysis of the skeletal facial profile was done measuring SNA, SNB and ANB angles. Rotation of the maxillary base (NS/SpP), rotation of the mandibular base (NS/MP) and vertical relationship between jaws (SpP/MP) were also measured. The results were statisticaly analysed using T test, descriptive statistics and Wilcoxon`s test. The results of this study showed changes in facial skeleton in children treated with Delair`s mask compared to the control group. In the first group of children SNA and ANB angles were increased and the SNB angle was decreased.